(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Learning difficulties, known as learning disabilities in North America, are conditions that impact on an individual’s ability to gain knowledge and skills at the same rate as his or her peers. They may be due to a mental handicap or a cognitive disorder. Having a learning difficulty does not make someone less intelligent, it just means they learn in a different way that can render traditional classroom activities problematic. That’s why students with learning difficulties require specific strategy training and customized lessons for overcoming challenges and make progress in an academic environment. The term “learning difficulties” includes a wide range of conditions from dyslexia and attention hyperactive deficit disorder (ADHD) to Down syndrome. Learning difficulties can affect children of all ages but they are particularly problematic for children who are learning how to read and write. This paper reflects study on Learning- difficulties of children.